BETTER METABOLIC OUTCOMES DELIVERED THROUGH A LIFESTYLE CARE PROGRAM IN PWD — EVIDENCE OF RETROSPECTIVE PILOT STUDY FROM URBAN INDIA - Sooragonda, Basavaraj; Fatema, Zareen; Kamat, Deepa; Narendra, BS; Sivarama , Dr (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES To assess the effect of a novel, personalized virtual diabetes care program, OneCare “IMPACT” program, on metabolic outcomes in PWD, among an urban south Indian cohort. METHODOLOGY A single-arm, retrospective, proof-of-concept study in PWD who enrolled in a 12-week virtual care program tailored to support diabetes self-management through personalized lifestyle education. The health coach remotely monitored patients through weekly scheduled calls to track progress. The patient's data, recorded by the coach, including HbA1c, weight, medications, and program engagement were used for the analysis. RESULTS A total of 41 patients with complete data were included for analysis. The mean age of the participants was 44.2 (± 12) years, 76% were male, median diabetes duration (years) of 1.3 (0.1–20), baseline HbA1c (%) of 9.5 (± 2.3), weight (kgs) of 74.6 (± 13.5). Decline in HbA1c (%) was 0.3 (SD 0.4, p <.001) with moderate effect size (d=0.53). HbA1c <7% was achieved in 54% while the clinician-decided target HbA1c was met in 61%. Mean weight (kgs) change was 2.5 (SD 2.7, p <.001) with large effect size (d=0.92). A significant short-term reduction in weight of ≥5% was achieved in 32% of patients. Majority (87%) had reduction in or continued same dose of diabetic medication at 12 weeks. The mean attendance was 83.6% and engagement fairly correlated with weight reduction, (-0.24, p=0.1) but not with decreasing HbA1c. CONCLUSION Clinically meaningful metabolic outcomes were achieved through the program with a high level of patient engagement in an urban Indian cohort. The study encourages well- designed RCT to confirm the effectiveness of the program.